2019
DOI: 10.3390/ijerph16091606
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Consumer’s Attitude toward Insect Food

Abstract: Given the influence of rising environmental awareness, food systems and security are receiving increasing international attention. Previous studies have discussed the acceptance of insect foods but have been primarily conducted in a European context. Hence, their results cannot be applied to Taiwanese consumers. Regarding this, our study is centered on the theory of planned behavior and considers environmental concern and food neophobia to discuss the effects of consumer attitudes, subjective norms, and percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 88 publications
1
25
1
Order By: Relevance
“…Consumers' PBC had a significant positive effect on their PI for fast food burgers (β = 0.014, p < 0.001), therefore H1c is tenable; that is, when consumers think that the purchase of vegetarian burgers is the right decision, their PI will increase. This result is in accordance with that of previous studies [20,22]. In addition, consumers' PK for vegetarian burgers had no significant relation with their PI (β = 0.235, p > 0.05), therefore H2 is not tenable; this result is inconsistent with that of previous studies [26][27][28]63].…”
Section: Hypothesis Testingcontrasting
confidence: 51%
See 3 more Smart Citations
“…Consumers' PBC had a significant positive effect on their PI for fast food burgers (β = 0.014, p < 0.001), therefore H1c is tenable; that is, when consumers think that the purchase of vegetarian burgers is the right decision, their PI will increase. This result is in accordance with that of previous studies [20,22]. In addition, consumers' PK for vegetarian burgers had no significant relation with their PI (β = 0.235, p > 0.05), therefore H2 is not tenable; this result is inconsistent with that of previous studies [26][27][28]63].…”
Section: Hypothesis Testingcontrasting
confidence: 51%
“…It includes the understanding of self-ability, urgent-need perception, and convenience perception [46,61]. Chang et al found that the PBC significantly affected consumers' intention to purchase insect foods [20]. Therefore, this study puts forward H1c: Consumer's PBC has a significant positive effect on the PI for artificial meat products.…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 80%
See 2 more Smart Citations
“…Socio-cultural factors determine the rejection of insects [ 28 , 30 ]. For most Western people insects are considered dirty, dangerous and disgusting, and they have an aversion to eating them [ 47 ]. The main perceived barriers are the sense of disgust arising from seeing insects and incompatibility with the local food culture [ 48 ].…”
Section: Resultsmentioning
confidence: 99%